Analysis Determination of Leading Sectors area Economy in the city Medan : LQ AND Shift Share Approach - Novianti Naomi Ulina Br. Naibaho; Venus Situmeang; Tasya Amelia Manurung (Outline Publisher, 2025)
This study aims to identify leading sectors in Medan City using the Location Quotient (LQ) and Shift-Share Analysis (SSA) methods with Gross Regional Domestic Product (GRDP) data from 2019 to 2023. Medan City, as a strategic economic center in North Sumatra, plays an important role in trade, industry, and services. This study uses secondary data from the Central Statistics Agency (BPS) of Medan City and North Sumatra to analyze economic sectors that contribute significantly to regional GRDP. Through the LQ method, this study successfully identified sectors that have higher competitive advantages compared to the national average, such as water supply, waste, construction, wholesale trade, transportation, accommodation, information and communication, and financial services.